The Differentiation of the Groups 4 e 5 of Municipalities in the state of São Paulo according to IPRS and Based on the Constitutional Transferences and Income Tributary Taxes - an Application of the Discriminant Analysis - Gouvêa, Maria Aparecida; Farina, Milton Carlos; Varela, Patrícia Siqueira (Review of Business Management, 2007)
This study intended to indicate whether the municipalities from São Paulo state, specifically the groups of municipalities characterized by the social responsibility index as municipalities with low richness index and intermediate social index (group 4) and municipalities disfavored in both conditions (group 5) can be distinguished by per capita transference values from the Municipalities Participation Fund – MPF, Product and Service Circulation Tax Quota (PSCT) and collected tributary income. The premise was the existence of the influence of the distribution of MPF on the performance of municipalities groups that serves as mechanism of income redistribution to compensate the smaller tributary capacity of the municipalities disfavored in richness. The behavior evaluation of the three types of public income in two selected groups of municipalities was carried out through discriminant analysis technique. The results become evident that the MPF distribution criteria contribute to the available income fairness in the municipalities of group 4, giving support to the municipalities government in the development of public policy. However, in the municipalities of group 5, this study indicates that the contribution is not effective or there are management problems in the resources allocation. Key-words: Discriminant analysis. Public income. Index from São Paulo state of social responsibility. Longevity. Educational instruction.